Desde las regiones: respuesta a la epidemia del COVID-19 de organizaciones indígenas regionales de la Amazonía peruana - Cárdenas Timoteo, Clara (2023)
The objective of this article is to point out the responses to covid-19 epidemic implemented by two Amazonian indigenous organizations at the regional level, orpio (Organización Regional de Pueblos Indígenas del Oriente) in the department of Loreto and fenamad (Federación Nativa of Madre de Dios) in the department of Madre de Dios, during the years 2020 to 2021, for which a qualitative study was carried out in which representatives of the aforementioned indigenous organizations were interviewed. The results reveal new forms of indigenous agency and advocacy on indigenous health issues, not only to claim the right to health care from the State, but also for the right to participate and be included in decision-making to face the epidemic. in indigenous peoples.